2019
DOI: 10.4317/medoral.22129
|View full text |Cite
|
Sign up to set email alerts
|

Dental care in children with Down syndrome: A questionnaire for Belgian dentists

Abstract: Background To date, research on the opinions of dentists on the oral health care of children with DS (Down Syndrome) is scarce. Material and Methods Evaluate the views and knowledge of Belgium dentists regarding dental care of children with DS. An adequate sample of dentists were invited to fill in a validated questionnaire. Results were assessed in 95% confidence interval with p < 0.05 level. Results A total of 356… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 11 publications
0
15
0
5
Order By: Relevance
“…In the present study, however, no such relation was found. The reason for this may be that in the study by Norderyd et al, only about 25% of the children with disabilities had DS [27].…”
Section: Dentistmentioning
confidence: 89%
See 1 more Smart Citation
“…In the present study, however, no such relation was found. The reason for this may be that in the study by Norderyd et al, only about 25% of the children with disabilities had DS [27].…”
Section: Dentistmentioning
confidence: 89%
“…Children who find it difficult to interact with people outside of the family have a greater need for customized dental care [25,26]. Therefore, these children often meet specialists in paediatric dentistry [27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, parents felt that health care professionals were reactionary towards their children, tried to avoid performing dental procedures, and kept their treatment limited to prescription of painkillers and antibiotics. It seems that health care professionals in primary dental care lack adequate knowledge and skills for providing oral health care for individuals with intellectual disability 32 . It is clear that more efforts are definitely needed to train dentists to manage oral health issues in patients with intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…These could arguably be one of the most important variables to consider when examining the impact sensory sensitivities may have on oral care, as uncooperative behaviors exhibited during care are reported to be one of the leading barriers to dentists' treatment of children with special healthcare needs. [35][36][37][38][39] Likewise, slightly more parents of children with SOR endorsed that their child had been refused care by a dentist due to their child's behavior problems than parents of SNOR children with DS.…”
Section: Discussionmentioning
confidence: 99%